Identification of gastrointestinal parasites in nonhuman primates of the Pucallpa Natural Zoological Park, Perú - Guerrero M., Francesca (2012)
The present study detected by stool examinations the presence of gastrointestinal parasites in nonhuman primates reared in captivity at the Pucallpa Natural Zoological Park, located in the department of Ucayali - Peru. A total of 72 collective fecal samples were collected from 58 individuals from species Cebus apella (brown capuchins), Saguinus fuscicollis weddelli (saddleback tamarins), Cebus albifrons (white-fronted capuchins), Lagothrix lagotricha (woolly monkey), Ateles paniscus chamek (spider monkey), Saimiri sciureus (squirrel monkey), Aotus nigriceps (black-headed night monkey) and Alouatta seniculus (red howler monkey). Samples were fixed in 10% formalin at 60 °C and analyzed by the direct method, and the Ritchie, Sheather, Sedimentation and Ziehl-Neelsen methods. Gastrointestinal parasites found were Strongyloides cebus (56/72), Paratriotaenia oedipomidatis (8/72), Prosthernorchis elegans (7/72), Trichostrongylidae (6/72), Oxyuroidea (2/72), Entamoeba coli (2/72), Coccidia oocysts (2/72), Cryptosporidium spp (3/72) and Balantidium coli (3/72). In the eight evaluated species, all had at least one parasite species.